Evaluation of the compactability of bituminous emulsion mixes: experimental device and methodology. Issue Volume 17:Issued 1(2016) (2nd January 2016) - Wendling, L.; Gaudefroy, V.; Gaschet, J.; Ollier, S.; Gallier, S.
Abstract : Laboratory asphalt mix design methodologies are aimed at predicting behaviour and determining characteristics of mixes. The French laboratory methodology for bituminous mixes is partially devoted to a compactability assessment. Samples are characterised by tests using the gyratory compactor. In this test, loose material is submitted to simultaneous compressive and shear forces, which lead to an internal aggregate reorganisation. The current French experimental device, called 'PCG3', was devoted strictly to hot mix asphalt characterisation. At present however, compactability properties of emulsion-treated gravel also appear as critical information due to the growing interest in bituminous cold mixes within an environmentally friendly context. A research project has been conducted in order to adapt the current 'PCG3' to allow for the compaction of cold mixes by adding the functionality of collecting extruded water due to emulsion breaking. This article is intended to describe this new device and determine the influence from adjusting parametric sensitivity on gravel treated with emulsion and compactability behaviour.